2021
DOI: 10.1002/mabi.202100098
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogels Based on Oxidized Cellulose Sulfates and Carboxymethyl Chitosan: Studies on Intrinsic Gel Properties, Stability, and Biocompatibility

Abstract: Cellulose and chitosan are excellent components for the fabrication of bioactive scaffolds, as they are biocompatible and abundantly available. Their derivatives Ocarboxymethyl chitosan (CMChi) and oxidized cellulose sulfate (oxCS) can form in situ gelling, bioactive hydrogels, due to the formation of imine bonds for crosslinking. Here the influence of the degrees of sulfation (DS), oxidation (DO), and the molecular weight of oxCS on intrinsic and rheological properties of such hydrogels and their ability to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…However, for biological studies in which cells are involved, these are suitable analyses on the condition that subsequent cell experiments are also carried out in PBS. Nevertheless, the absence of nutrient content in this buffer has detrimental effect on the viability of certain cell lines when embedded in hydrogels prepared in PBS, [ 25 ] making necessary to work with cell culture media. In our previous work on different strategies to crosslink GelMA macromer and their impact in the mechanical and biological properties of the bioscaffolds, we also observed the RM had an impact on the mechanical properties.…”
Section: Resultsmentioning
confidence: 99%
“…However, for biological studies in which cells are involved, these are suitable analyses on the condition that subsequent cell experiments are also carried out in PBS. Nevertheless, the absence of nutrient content in this buffer has detrimental effect on the viability of certain cell lines when embedded in hydrogels prepared in PBS, [ 25 ] making necessary to work with cell culture media. In our previous work on different strategies to crosslink GelMA macromer and their impact in the mechanical and biological properties of the bioscaffolds, we also observed the RM had an impact on the mechanical properties.…”
Section: Resultsmentioning
confidence: 99%
“…According to Willems et al., 2021, the degradation of the hydrogel systems composed of oxidized cellulose sulfates and carboxymethyl chitosan is less pronounced with higher levels of the oxidized polymer. [ 7 ] It is noted that the degradability and swelling abilities of the hydrogel under impacts from the level of cross‐linkage had certain correlations. The degradation of a hydrogel can be prolonged as the water content decreases.…”
Section: Resultsmentioning
confidence: 99%
“…[2][3][4] By employing in situ crosslinkable with pre-modifying the polymer chains with functional groups liable to be crosslinked, the efficiency of a crosslinked hydrogel formation can be increased and thus enhance their durability and stability. Dynamic hydrogels from carboxymethyl chitosan (CMC) have been investigated in the past years, including CMC/oxidized sodium alginate, [5] CMC/oxidized hyaluronic acid, [6] and CMC/oxidized cellulose sulfates hydrogels [7] which have facilitated their widespread use in many applications in biomedical engineering. Recently, a promising material from aldehydemodified xanthan and carboxymethyl-modified chitosan has been reported by Huang et al, 2018 which showed potential applications for a local drug delivery system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polysaccharides are the most abundant biopolymers in nature and because of their plentiful availability, relatively low production costs, and particularly their inherent bioactivity, they represent ideal candidates for making hydrogels and scaffolds to be used in tissue engineering [6]. Because of the presence of different functional groups, such as hydroxyl and carboxyl groups, polysaccharides can also be easily chemically modified to add specific functions to tailor their properties to different applications [7][8][9]. Hyaluronic acid (HA), for example, is a component of the extracellular matrix in mammalian tissues.…”
Section: Introductionmentioning
confidence: 99%